KREASI KERAMIK HANDBUILT DENGAN INSPIRASI DARI ADAT PERNIKAHAN SUNDA: DESIGN OF HANDBUILT CERAMIC PRODUCTS INSPIRED BY SUNDANESE WEDDING CEREMONY - Susi Hartanto; Gaby Inetta; Geoffrey Tjakra (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Design of Handbuilt Ceramic Products Inspired by Sundanese Wedding Ceremony The Sundanese ethnic group, originating from West Java, possesses a rich culture with symbols and ideas that remain relevant into the modern era. The cultural symbolism serves as inspiration for creating household ceramic products using handbuilt techniques. The research process involves steps such as literature review, qualitative research, data analysis, and design development. The final products include flower vases, pitchers, and candle holders adorned with the theme of "bunga tujuh rupa" to represent symbols, hopes, and meanings in Sundanese weddings. These products not only serve as decorations but also act as reminders of the cultural significance of Sundanese weddings, allowing for celebration and honoring of the event. The importance of meaning in design is emphasized, ensuring that each component carries sentimental value and represents hopes and prayers. The conclusion underscores the satisfaction of looking back at special moments through beautiful memories, reminding us of the intrinsic value of meaningful products.